1997
DOI: 10.1021/om960578a
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Palladium and Platinum Complexes Containing Rigid Bidentate Nitrogen Ligands and Electrochemistry of the Palladium Complexes1

Abstract: Divalent palladium and platinum complexes containg rigid bidentate nitrogen ligands and electrochemistry of the palladium complexes van Asselt, R.; Elsevier, C.J.; Amatore, CH.; Jutand, A. Published in: Organometallics DOI:10.1021/om960578aLink to publication Citation for published version (APA):van Asselt, R., Elsevier, C. J., Amatore, C. H., & Jutand, A. (1997). Divalent palladium and platinum complexes containg rigid bidentate nitrogen ligands and electrochemistry of the palladium complexes. Organometallics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 58 publications
(48 reference statements)
4
45
0
6
Order By: Relevance
“…Diagnostic of chelating ligand coordination in these complexes is the downfield shift in the 1 HNMR spectra of the imine signal by 0.3-0.4 ppm upon coordination to the Pd(II) centre. Similar shifts have been observed in related compounds [18,25,[30][31][32]. The imine signals in the 13 CNMR spectra also show a downfield shift of 10.1-16.3 ppm upon metal coordination.…”
Section: Characterization Of the Ligands And Complexessupporting
confidence: 79%
“…Diagnostic of chelating ligand coordination in these complexes is the downfield shift in the 1 HNMR spectra of the imine signal by 0.3-0.4 ppm upon coordination to the Pd(II) centre. Similar shifts have been observed in related compounds [18,25,[30][31][32]. The imine signals in the 13 CNMR spectra also show a downfield shift of 10.1-16.3 ppm upon metal coordination.…”
Section: Characterization Of the Ligands And Complexessupporting
confidence: 79%
“…[46] The Ar-BIAN system is a highly stable, rigid bidentate spectator ligand with interesting electronic properties. [47,48] Elsevier and co-workers suggested that Ar-BIAN ligands may act as stronger σ-donors toward the metal when compared to bpy, and also proposed that the rigid Ar-BIAN ligands are rather comparable to open chain R-DAB analogues in electronic properties, which would be the case if the diimine system in the Ar-BIAN ligands is electronically isolated from and has no conjugation with the naphthalene backbone. [35] The capacity of this ligand type to support many oxidation states has been amply demonstrated; for example, Pt Ar-BIAN complexes have been reported in oxidation states ranging from Pt 0 [35] via Pt II [45] to Pt IV .…”
Section: Introductionmentioning
confidence: 99%
“…[3] A series of further rigid 1,4-bidentate ligands, [4] diferrocenyl-substituted 1,5-bidentate ligands [5] and non-rigid 1,4-nitrogen ligands with ferrocenyl Schiff-base units, [6] as well as a few interesting mononuclear zinc, copper, [6] nickel, [7] platinum [8] and binuclear palladium and platinum [9] complexes have also been described. The number of known examples of nitrogen-containing macrocycles with two bridged ferrocene units is, however, limited.…”
Section: Introductionmentioning
confidence: 99%